Tracheobronchial deposition of inhaled particles in rabbits. - Tomenius, Lennart (Scandinavian Journal of Work, Environment & Health, 1977)
Tracheobronchial deposition of inhaled particles in rabbit lung was studied after exposure to monodisperse aerosols 4--9 micrometer (aerodynamic diameter). Deposition was measured in terms of the particle content in free dissected bronchial sections from formaldehyde exposed and dried lungs. The free dissected part consisted of the lower section of the trachea and the lobe bronchi with their extensions from the five lobes. Deposition in this part of the tracheobronchial tree varied according to particle size, exposure technique, and individual. The range of the individual variation was about the same (300%) as the difference in deposition caused by changes in particle size (4 to 7 micrometer) and exposure technique (tracheal or oral tube). The individual variation could not be explained by any physiological factor, such as contraction in the respiratory tract. Rabbits treated intravenously with atropin had the same tracheobronchial deposition as a control group. On the other hand the individual variation in deposition could be explained by some anatomical factor since airway diameter and bronchial deposition showed a significant negative correlation.
Keywords: aerosol; bronchus; deposition; inhaled particle; lung; particle; rabbit; tracheobronchial deposition